Analysis of Liquefaction Potential Based on SPT and CPT Data in the Yogyakarta International Airport Area - Abul Fida Ismaili; Adwiyah Asyifa (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
The occurrence of earthquakes will cause damage to building structures as well as damage to soil structures. One of the impacts is Liquefaction, which is a process or event of changing the state of the soil from a solid state to a liquid state caused by a cyclic load at the time of the earthquake so that there is a change in the voltage in the soil. Analysis method of potential liquefaction using simplified method, based on SPT and CPT data. From the data, cyclic stress ratio (CSR), Cyclic Resistant Ratio (CRR) and security factors were obtained. Based on the calculation analysis, it is known that there is a potential liquefaction in YIA area with different depth variations according to the location of data retrieval with an earthquake magnitude of 7.5 SR.